The Principal's Strategy for Improving the Quality of Education: A Study at MTs Asy-Asyafiiyah Kendari - Nadia Ayu Pratiwi (Shautut Tarbiyah, 2020)
This article aims to describe: 1) the strategy of the madrasah head in improving the quality of education in MTs Asy-Syafiiyah Kendari; 2) supporting and inhibiting factors in improving the quality of education in MTs Asy-Syafiiyah Kendari; 3) the impact of implementing the Madrasah Kapala strategy on improving the quality of education in Ass-Asyafiiyah Kendari MTs. This research is a qualitative research, in which data is collected through interviews, observations, and document studies. The collected data is analyzed through the process of data reduction, data display, and data verification. The results showed: 1) the principal's strategy in improving the quality of education is seen in the vision and policies of quality-oriented schools, exploring student competencies, developing teacher competencies, and establishing partnerships; 2) a supporting factor in improving the quality of education is the leadership of the principal who focuses on the quality and support of the community. While the inhibiting factors are quality awareness not yet evenly distributed to all school residents; 3) The principal's strategy has an impact on the recognition of MTs Asy-Syafiiyah by the community, increasing graduation rates, increasing work partners, improving the development of students' talent interests, and increasing teacher competency. Keywords: Madrasah Head Strategy, Quality of Education